2015
DOI: 10.1111/jfb.12801
|View full text |Cite
|
Sign up to set email alerts
|

Sperm traits in farmed and wild Atlantic salmon Salmo salar

Abstract: Differences in sperm metabolism and morphology between wild and non-local farmed Atlantic salmon Salmo salar were assessed by measuring metabolic enzyme activities and length of sperm flagella. No differences were observed between wild and farmed S. salar sperm with regards to cell counts or any of the biochemical variables assessed. Flagella of sperm cells were significantly longer in wild than farmed S. salar; however, this did not result in higher energy levels or different fertilization rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Moreover, males with less ornamentation had higher sperm motility and greater fertilization success, but produced less viable embryos (Kekäläinen et al 2015). Differences in competitive ability of sperm may in part explain differences in reproductive success between hatchery and wild males; however, Camarillo- Sepulveda et al (2015) found most sperm characteristics of wild and farmed Atlantic salmon similar with the exception of wild salmon sperm having a longer flagellum, but this did not translate into increased fertilization rates. Their study had a relatively low sample size of 10 wild males, 21 farmed males, and 8 females each of wild and farmed origin.…”
Section: Post-spawning Sexual Selectionmentioning
confidence: 96%
“…Moreover, males with less ornamentation had higher sperm motility and greater fertilization success, but produced less viable embryos (Kekäläinen et al 2015). Differences in competitive ability of sperm may in part explain differences in reproductive success between hatchery and wild males; however, Camarillo- Sepulveda et al (2015) found most sperm characteristics of wild and farmed Atlantic salmon similar with the exception of wild salmon sperm having a longer flagellum, but this did not translate into increased fertilization rates. Their study had a relatively low sample size of 10 wild males, 21 farmed males, and 8 females each of wild and farmed origin.…”
Section: Post-spawning Sexual Selectionmentioning
confidence: 96%
“…Experimental studies have shown that there are significant differences in sperm morphology (Gage et al, 2004;Gage, Stockley, & Parker, 1998) and fertilization success among individual males (Gage et al, 2004). However, when farmed and wild salmon have been reared under identical conditions (Yeates, Einum, Fleming, Holt, & Gage, 2014), or taken directly from farms and from the wild (Camarillo-Sepulveda et al, 2016), no systematic differences in sperm and egg quality or in vitro fertilization success have been observed between farmed and wild salmon. This leads to the conclusion that if individual farmed escaped adults manage to partake in spawning in the wild, despite their general competitive inferiority, they will have similar fertilization success to wild adults.…”
Section: Do Farmed Escapees Spawn In the Wild?mentioning
confidence: 99%
“…salar (Lush et al ., ). On the other hand, results on sperm quality of farm and wild males suggest no disparities in sperm traits and near functional equivalence (Camarillo‐Sepulveda et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…So far, results show that unfertilized eggs of farm Saint John River S. salar are smaller, weigh less and contain less energy in the form of ATP and may have lower fertilization success than wild Little River S. salar (Lush et al, 2014). On the other hand, results on sperm quality of farm and wild males suggest no disparities in sperm traits and near functional equivalence (Camarillo-Sepulveda et al, 2016).…”
Section: Introductionmentioning
confidence: 99%